2017
DOI: 10.1016/j.appet.2017.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of dark chocolate attenuates subsequent food intake compared with milk and white chocolate in postmenopausal women

Abstract: Dark chocolate attenuates subsequent food intake in postmenopausal women, compared to the impact of milk and white chocolate consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Consistent with our results, it has been observed that a diet enriched in flavonoids (provided by dark chocolate, dehydrated apple and green tea; giving an approximate daily dose of epicatechin of 425 mg), added to antihypertensive treatment, decreases leptin levels in young hypertensive patients 51 . By contrast, acute intake of dark chocolate failed to modify leptin levels in postmenopausal women 52 .…”
Section: Journal Name Articlementioning
confidence: 78%
“…Consistent with our results, it has been observed that a diet enriched in flavonoids (provided by dark chocolate, dehydrated apple and green tea; giving an approximate daily dose of epicatechin of 425 mg), added to antihypertensive treatment, decreases leptin levels in young hypertensive patients 51 . By contrast, acute intake of dark chocolate failed to modify leptin levels in postmenopausal women 52 .…”
Section: Journal Name Articlementioning
confidence: 78%
“…For example, cocoa pods collected from T. cacao are processed into nibs, cocoa liquor, cocoa butter, and cocoa powder, then alkalized to improve solubility, alter color, and modify flavor ( 63 ). The resulting variable changes in amino acids ( 64 ), polyphenols ( 65 ), methylxanthines including theobromine ( 66 ), and other functional compounds of cocoa products ( 63 ) contradict our goal to test a simple cocoa extract supplement that preserves the known bioactive contents of the cocoa bean without adding excessive sugar, saturated fat, and calories ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the volunteers had an increase of energy intake due to chocolate’s extra calories (extra 542 kcal) as compared to the non‐chocolate condition, they spontaneously reduced their ad libitum energy intake by 16% when eating chocolate in the morning. This happened even though females consumed milk chocolate that has been shown to have less of an effect in decreasing appetite than dark chocolate 31 . Specific components of chocolate, such as epicatechin, may be accounting for this compensatory effect 32 .…”
Section: Discussionmentioning
confidence: 99%
“…This happened even though females consumed milk chocolate that has been shown to have less of an effect in decreasing appetite than dark chocolate. 31 Specific components of chocolate, such as epicatechin, may be accounting for this compensatory effect. 32 Indeed, participants had an increase in total polyphenols of 854.3 mg (mainly epicatechin and catechin) per day due to milk chocolate (100 g), while no differences were found in the other polyphenols content in the rest of the diet, when eating ad libitum.…”
Section: Discussionmentioning
confidence: 99%